Sleep Parameters, Functional Status, and Time Post-Stroke are Associated with Offline Motor Skill Learning in People with Chronic Stroke - Siengsukon, Catherine; Al-Dughmi, Mayis; Al-Sharman, Alham; Stevens, Suzanne (Frontiers in Neurology, 2015)
Background: Mounting evidence demonstrates that individuals with stroke benefit from sleep to enhance learning of a motor task. While stage NREM2 sleep and REM sleep have been associated with off-line motor skill learning in neurologically-intact individuals, it remains unknown which sleep parameters or specific sleep stages are associated with off-line motor skill learning in individuals with stroke. Methods: Twenty individuals with chronic stroke (> 6 months following stroke) and 10 neurologically slept for three consecutive nights in a sleep laboratory with polysomnography. Participants practiced a tracking task the morning before the third night and underwent a retention test the morning following the third night. Off-line learning on the tracking task was assessed. Pearson’s correlations assessed for associations between the magnitude of off-line learning and sleep variables, age, upper extremity motor function, stroke severity, depression and time since stroke occurrence. Results: Individuals with stroke performed with significantly less error on the tracking task following a night of sleep (p=.006) while the control participants did not (p=.816). Increased sleep efficiency (r= -.285), less time spent in stage NREM3 sleep (r=.260), and more time spent in stage REM sleep (r= -.266) was weakly-to-moderately associated with increased magnitude of off-line motor learning. Furthermore, higher upper-extremity motor function (r = -.400), lower stroke severity (r = .360), and less time since stroke occurrence (r=.311) were moderately associated with increased magnitude of off-line motor learning. Conclusion: This study is the first study to provide insight into which sleep stages and individual characteristics may be associated with off-line learning in people with stroke. Future work should continue to understand which factors or combination of factors promote off-line motor learning in people with neurologic injury to best promote motor recovery in these individuals.